2019
DOI: 10.4163/jnh.2019.52.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of ethanol extract ofLycium barbarum'sleaf with removal of chlorophyll

Abstract: Purpose: The aim of this study was to estimate the antioxidant activities of 50%, 70%, and 100% ethanol extracts of Lycium barbarum leaf and chlorophyll removal extract. Methods: The antioxidant activities were estimated by measuring total polyphenol content and by assays of 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2'-azino-bis (3-ethylbenzothiazoline-6-sulfate) (ABTS) radical scavenging activities and ferric reducing antioxidant power (FRAP). In addition, reactive oxygen species (ROS) production, DNA fragme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…[ 17 ] measured the degree of DNA damage after administration of L. barbarum leaf ethanol extracts or chlorophyll-removed ethanol extract in BALB/c mice with an lipopolysaccharide-induced inflammatory response and found that there was no significant difference between the 2 groups. In another study examining the antioxidant efficacy of L. barbarum leaf ethanol extract in HepG2 cells, it was shown that the antioxidant activity of chlorophyll-removed ethanol extract of L. barbarum leaves was higher than that of the ethanol extract of L. barbarum leaf before the removal of chlorophyll [ 16 ]. In that previous study, the yield, chlorophyll content, and total polyphenol content of the 2 ethanol extracts of L. barbarum leaf (LLE and LLE[Ch-]) were reported.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[ 17 ] measured the degree of DNA damage after administration of L. barbarum leaf ethanol extracts or chlorophyll-removed ethanol extract in BALB/c mice with an lipopolysaccharide-induced inflammatory response and found that there was no significant difference between the 2 groups. In another study examining the antioxidant efficacy of L. barbarum leaf ethanol extract in HepG2 cells, it was shown that the antioxidant activity of chlorophyll-removed ethanol extract of L. barbarum leaves was higher than that of the ethanol extract of L. barbarum leaf before the removal of chlorophyll [ 16 ]. In that previous study, the yield, chlorophyll content, and total polyphenol content of the 2 ethanol extracts of L. barbarum leaf (LLE and LLE[Ch-]) were reported.…”
Section: Discussionmentioning
confidence: 99%
“…In that previous study, the yield, chlorophyll content, and total polyphenol content of the 2 ethanol extracts of L. barbarum leaf (LLE and LLE[Ch-]) were reported. As 99.8% of chlorophyll was removed from LLE(Ch-), the yield decreased from 20.5% to 16.45%, and the total polyphenol content more than doubled (140.5 ± 7.45 mg gallic acid equivalent [GAE]/extract g vs. 312.9 ± 10.2 mg GAE/extract g) [ 16 ]. Also, the content of flavonoid, a type of polyphenol, increased from 34.77 ± 1.29 mg catechin equivalents (CE)/g to 42.75 mg CE/g (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations